Comparison of Percutaneous Endoscopic Lumbar Discectomy and Open Lumbar Microdiscectomy for Recurrent Disc Herniation - Lee, Dong Yeob (The Korean Neurosurgical Society, 2009)
OBJECTIVE: The purpose of this study was to compare clinical and radiological outcomes of percutaneous endoscopic lumbar discectomy (PELD) and open lumbar microdiscectomy (OLM) for recurrent disc herniation. METHODS: Fifty-four patients, who underwent surgery, either PELD (25 patients) or repeated OLM (29 patients), due to recurrent disc herniation at L4-5 level, were divided into two groups according to the surgical methods. Excluded were patients with sequestrated disc, calcified disc, severe neurological deficit, or instability. Clinical outcomes were assessed using Visual Analogue Scale (VAS) score and Oswestry Disability Index (ODI). Radiological variables were assessed using plain radiography and/or magnetic resonance imaging. RESULTS: Mean operating time and hospital stay were significantly shorter in PELD group (45.8 minutes and 0.9 day, respectively) than OLM group (73.8 minutes and 3.8 days, respectively) (p < 0.001). Complications occurred in 4% in PELD group and 10.3% in OLM group in the perioperative period. At a mean follow-up duration of 34.2 months, the mean improvements of back pain, leg pain, and functional improvement were 4.0, 5.5, and 40.9% for PELD group and 2.3, 5.1, and 45.0% for OLM group, respectively. Second recurrence occurred in 4% after PELD and 10.3% after OLM. Disc height did not change after PELD, but significantly decreased after OLM (p = 0.0001). Neither sagittal rotation angle nor volume of multifidus muscle changed significantly in both groups. CONCLUSION: Both PELD and repeated OLM showed favorable outcomes for recurrent disc herniation, but PELD had advantages in terms of shorter operating time, hospital stay, and disc height preservation.